Rough Set Rules Extraction for Student Programming Skills - Kerwad, Mokhtar Massoud (2006)
Programming is a critical subject to computer science or information technology students. It is one of the fundamental skills they need to acquire during study. The aim of the study is to generate a compact set of rules using real data to predict student's performance. Not all variables as usual if good results are to be obtained. Data mining refers to one of the phases or step within the knowledge discovery in databases (KDD) processes for extracting used rough set technique. The extracted rules will be a measurement of the students' performance in programming and give the insight to educators on what should be help the students to master programming skills.